2017
DOI: 10.1002/mds.27193
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of genetic synucleinopathies with parkinsonism: Review of the literature

Abstract: Clinical-pathological studies remain the gold-standard for the diagnosis of Parkinson’s disease (PD). However mounting data from genetic-PD autopsies challenge the diagnosis of PD based on Lewy body pathology. Most of the confirmed genetic risks for PD show heterogenous neuropathology, even within kindreds, which may or may not include Lewy body pathology. Here we review the literature of genetic-PD autopsies from cases with molecularly-confirmed PD or parkinsonism and summarize main findings on SNCA (n=25), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
234
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(248 citation statements)
references
References 176 publications
10
234
1
3
Order By: Relevance
“…Because there was only 1 genetic case in our cohort, we could only speculate that the CSF α-syn RT-QuIC test might not be suitable for detecting all patients with a genetic form of PD, as autopsy reports of genetic (including PARK2) PD cases have shown that Lewy bodies may be either present or absent. 17 Unexpected positive test results were found in 5 of 79 cases. The 1 PSP patient with a positive test result was a patient who, at disease onset, had clinical MSA-like features with prominent autonomic features (unusual for PSP), but at follow-up had clinical features that were more PSP-like (including supranuclear gaze palsy).…”
Section: May 2019mentioning
confidence: 94%
“…Because there was only 1 genetic case in our cohort, we could only speculate that the CSF α-syn RT-QuIC test might not be suitable for detecting all patients with a genetic form of PD, as autopsy reports of genetic (including PARK2) PD cases have shown that Lewy bodies may be either present or absent. 17 Unexpected positive test results were found in 5 of 79 cases. The 1 PSP patient with a positive test result was a patient who, at disease onset, had clinical MSA-like features with prominent autonomic features (unusual for PSP), but at follow-up had clinical features that were more PSP-like (including supranuclear gaze palsy).…”
Section: May 2019mentioning
confidence: 94%
“… Atypical park: atypical parkinsonism; AD, autosomal dominant; AR, autosomal recessive; X‐linked R/D, X‐linked recessive/ dominant; *, in SNCA duplications; α, (Marras et al, ); #, Adapted (Vincenzo Bonifati, ); ß: (Schneider and Alcalay, ). …”
Section: The Genetic Landscape Of Pdmentioning
confidence: 99%
“…As such, neuropathological criteria for definite diagnosis of PD have included the loss of dopaminergic neurons in the SNc and the presence of Lewy pathology (Daniel and Lees, 1993) (Gelb, Oliver, and Gilman, 1999) (Dickson et al, 2009). Neuropathological studies in genetic forms of PD challenge this concept: SNCA-related PD cases have presented tau inclusions, TDP-43 inclusions in neurites and cell bodies in the temporal cortex (Markopoulou et al, 2008) or MSA-like features (Pasanen et al, 2014); G2019S-related PD cases have been found to have no Lewy pathology (Poulopoulos, Levy, and Alcalay, 2012);and PRKN is associated with none or little asynuclein deposition (Schneider and Alcalay, 2017).…”
Section: Evidence From Neuropathological Studiesmentioning
confidence: 99%
“…These criteria are matched by the majority of people with Parkinson's disease carrying mutations in LRRK2 . A subset, however, and perhaps as high as 1 in 10, diverge from this canonical pathology (Schneider & Alcalay, ). This was noted in one of the original papers reporting the identification of mutations in LRRK2 , describing pleiomorphic pathology in a kindred from western Nebraska.…”
Section: Introductionmentioning
confidence: 99%